The thermal implications and ecological consequences of coloration in selected species : tenebrionid beetles (Onymacris bicolor and Onymacris ungui cularis), Cape gannets (Morus capensis) and Cape cormorants (Phalacrocorax capensis) - Lombard, Amanda T (Department of Biological Sciences, 2014)
Bibliography: leaves 176-192.